2006
DOI: 10.1111/j.1467-7687.2006.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

The shape of boubas: sound–shape correspondences in toddlers and adults

Abstract: A striking demonstration that sound-object correspondences are not completely arbitrary is that adults map nonsense words with rounded vowels (e.g. bouba) to rounded shapes and nonsense words with unrounded vowels (e.g. kiki) to angular shapes (Köhler, 1947; Ramachandran & Hubbard, 2001). Here we tested the bouba/kiki phenomenon in 2.5-year-old children and a control group of adults (n =20 per age), using four pairs of rounded versus pointed shapes and four contrasting pairs of nonsense words differing in vowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
470
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(494 citation statements)
references
References 20 publications
17
470
0
7
Order By: Relevance
“…While the bouba-kiki effect is detected in infants around 11-adults (e.g., Maurer et al, 2006;Imai et al, 2008;Imai & Kita, 2014;Spence, 2011;etc. ), young infants only show sensitivities to arbitrary speech-sound correspondences before 6 months of age under specific circumstances (Experiment 1 of this study; Fort et al, 2013;Ozturk et al, 2013 when using non-words with syllable repetitions).…”
Section: Discussionmentioning
confidence: 99%
“…While the bouba-kiki effect is detected in infants around 11-adults (e.g., Maurer et al, 2006;Imai et al, 2008;Imai & Kita, 2014;Spence, 2011;etc. ), young infants only show sensitivities to arbitrary speech-sound correspondences before 6 months of age under specific circumstances (Experiment 1 of this study; Fort et al, 2013;Ozturk et al, 2013 when using non-words with syllable repetitions).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to override linguistic and cultural boundaries, and does not appear to be dependent on familiarity with particular letter shapes. Recent studies have shown the effect in 4 month old infants (Ozturk, Krehm & Vouloumanos, 2013), pre-lexical toddlers (Maurer, Pathman & Mondlock, 2006) and populations that have no written language (Bremner et al, 2012). The "Bouba-Kiki" effect has even been extended to include associations between words and taste.…”
Section: Discussionmentioning
confidence: 99%
“…The rounded outline of the letters B and O in "Bouba", for example, might encourage an Touching Words November 2013 N 2 association with the rounded shape, while the spiky forms of the letters K and I in "Kiki" would do the same for the jagged shape. To this end, Maurer, Pathman and Mondlock (2006) asked pre-lexical toddlers to associate four pairs of rounded/spiky shapes (3 pairs of 2D drawings/cut-out shapes and one pair of 3D objects modelled in clay) with four pairs of contrasted nonsense words differing in their vowel sound. Although overall the toddlers' bias was not as strong as that of a control group of adults, perhaps simply due to noise in the data, the youngsters still associated the rounded forms more consistently with rounded vowel sounds, and angular forms with non-rounded vowel sounds than would have been expected by chance.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we determined whether systematicity is differently expressed in the vocabulary across stages of language development. If sound symbolism is critical for language acquisition [8,50], then we would predict greater systematicity for words that are implicated in early language acquisition than those related to later language use. We related each individual monomorphemic word's systematicity to the estimated age at which it was acquired, controlling for other psycholinguistic variables [47] Figure 5 illustrates the mean systematicity for words binned into age of acquisition years from age 2 to 13 and older (note that words are not reliably judged to be acquired before 2 years old).…”
Section: (B) Arbitrariness Of Individual Wordsmentioning
confidence: 91%